SOCIAL MARKETING IN PROMOTING HEALTH BEHAVIOR: A ROLE OF PSYCHOLOGICAL SET - Conny Tjandra R; Jofi Puspa (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2012)
AbstractIncreasingly incidences of nutrition related diseases such as cardiovascular diseases, obesity and cancers are becoming significant health burdens not only in western countries but it is also newly coming health problem in Asia, including Indonesia. To encounter this development in the future it is important to continually promote the diseases prevention actions through appropriate social marketing programs. For that purpose, understanding psychological set such as knowledge, belief, attitude and motivation to perform diseases prevention actions and their causal relationship is becoming more and more important. The most challenging issue is to perform social marketing programs that can successfully influence people future health behavior. Our study has aim to understand the relationship of some psychological factors in influencing behavior. The result of this study showed that in spite of controversial issues published in current studies, we found that inherent knowledge level influences motivation through a modulation of attitude variable.Keywords: eating behavior, knowledge, attitude, motivation, behavioral action, prevention, healthy eating habit.AbstrakMeningkatnya jumlah penyakit kronik yang berhubungan dengan gizi pangan seperti penyakit jantung koroner, kegemukan dan kanker merupakan masalah kesehatan yang utama bukan hanya di Negara barat saja melainkan juga terjadi di negara berkembang seperti Asia. Untuk mengatasi masalah ini, perlu dikembangkan sistem pencegahan yang dapat dilakukan oleh setiap individu didalam masyarakat. Pendidikan dan penyuluhan kepada masyarakat terhadap pentingnya tindakan preventif seperti melalui “social marketing programs” yang digalakkan baik oleh pemerintah atau institusi kesehatan lainnya, sangatlah penting. Didalam social marketing, promosi tentang pencegahan semestinya dilakukan dengan terlebih dahulu mengetahui dan mengenal segala macam bentuk kebutuhan dasar, pengetahuan, sikap, kepercayaan dan faktor psikologi lainnya dari masyarakat. Studi ini bertujuan untuk mengetahui peran pengetahuan nutrisi, sikap dan motivasi masyarakat Indonesia (Jawa) terhadap upaya pencegahan penyakit kronik. Salah satu hasil utama dari penelitian ini menunjukkan bahwa pengetahuan dasar konsumen akan mempengaruhi motivasi secara tidak langsung melalui pembentukan sikap konsumen.Kata Kunci: perilaku konsumen, motivasi, pengetahuan,sikap, pencegahan penyakit, pola makan sehat.